The Edges of the Earth in Ancient Thought : Geography, Exploration, and Fiction - Romm, James S. (Book collections on Project MUSE., 1992)
The "edges of the earth" became the basis of a literary tradition, surveyed here, revealing that the Greeks, and to a somewhat lesser extent the Romans, saw geography not as a branch of physical science but as an important literary genre.